PROBLEMATIKA KEPALA SEKOLAH DALAM MELAKSANAKAN SUPERVISI AKADEMIK: SEBUAH TINJAUAN KONSEPTUAL DAN PRAKTIS: Kualitatif Deskriptif - Holilah, Enong; Ida Apriani, Nur; Rosmilawati, Ila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Academic supervision is a key function of the principal’s instructional leadership aimed at improving the quality of teaching through continuous professional guidance for teachers. However, its implementation faces various complex challenges, both from the principal’s internal factors and external aspects such as the school environment and the educational system. This study employs a descriptive qualitative approach through comprehensive literature analysis to identify these obstacles, including conceptual misunderstandings, limited competence and time, teacher resistance, and inadequate planning and follow-up. The findings reveal that the root cause lies in a paradigm of supervision that remains oriented toward administrative evaluation rather than professional coaching. The impact of these problems includes non-objective teacher performance assessments, hindered professional development, stagnation in instructional quality, and a deteriorating school climate. As solutions, this study recommends enhancing principals’ supervisory competence through intensive training, developing systematic and participatory supervision plans, building a trust-based collaborative culture, utilizing technology to improve supervisory efficiency, and strengthening systemic support from school supervisors and education authorities. Implementing these recommendations is expected to restore the essence of academic supervision as a strategic instrument for promoting teacher professionalism and improving educational quality in schools sustainably.